BACTERIOGICAL PROFILE OF CRITICALLY ILL PATIENTS IN INTENSIVE CARE UNIT IN BANGALORE - N, SHRUTHI; KUMAR M, RAVISH; KT, RAMESHA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Intensive care units (ICUs) are considered as the epicentre of infections due to its vulnerable conditions for development, amplification, and dissemination of drug-resistant microorganisms. Furthermore, the use of inappropriate or incorrect antibiotics is also closely related to development and spread of drug-resistant microorganisms. Hence, the present study was conducted in a private hospital in South Bangalore, to evaluate the spectrum of micro organisms isolated from clinical samples of patients admitted in ICU and their antimicrobial susceptibility pattern. Methods: This observational study was conducted on critically ill patients admitted in medical ICUs of private hospital in south Bangalore, Karnataka, India. The study was designed to include all patients with age 18 years or older, admitted for more than 48 h in medical ICUs of the hospital and having at least two of the clinical signs of SIRS. Depending on the clinical suspicion, clinical samples such as pus, blood, urine, body fluids, respiratory specimen were collected. The samples collected were first subjected to gram staining and then were inoculated on blood agar and MacConkey agar plates taking proper aseptic precautions. Antimicrobial sensitivity patterns of respective organisms were studied on Mueller Hinton agar media by Kirby Bauer’s disk diffusion method. Results: A total of 665 clinical samples were received in the microbiology laboratory out of which 60% samples showed significant microbial growth. The most predominant isolates were Gram-negative organisms 72.68% and Gram-positive isolates were seen in 27.3%. Sample-wise distribution of positive culture was done. Pus 33%, respiratory specimen 26%, urine 20%, blood 15%, and body fluids 6%. Majority of Gram-negative isolates were susceptible to amikacin, followed by piperacillin/tazobactum, cefeperazone/salbactum and imipenem and high resistance rates to ampicillin, amoxy clav was noted. Most of the Staphylococcus aureus were sensitive to linezolid, vancomycin, followed by amikacin, pipercillin/tazobactum, and cefeperazone/salbactum. Conclusion: The present study showed the high prevalence of aerobic bacteria in clinical samples of critically ill patients in ICUs. The study identified both Gram-positive and Gram-negative organisms to be responsible for causing blood stream infections. There should be continuous surveillance of data of clinical isolates along with their sensitivity pattern with routine surveillance for baseline resistance, stringent hospital infection policy, and their implementation in the hospital is the need of the hour to stop or reduce drug resistance.